Artful Representations as Productive Resistance: Researcher Learnings in Expanding Boundaries of Critical Methodology in Speech-Language Pathology - Kristen Abrahams (SAGE Publishing, 2021)
In this paper, we engage in productive resistance through exploring the application of an arts-based method in expanding the critical research methodology repertoire in the profession of speech-language pathology. There is a specific focus on the value of painting in the data representation process. We explore how a playful, creative analysis deepened the critical interpretative meaning-making process. In particular, we explain how artful representations in the data analysis process can broaden communication in research beyond the written modality to generate alternative knowledges. We use the concepts of productive ambiguity and unknowing as key conceptual tools to reimagine the data analysis process with particular focus on the process of data representation. We conclude that embracing the uncertainty of creative ways of knowing create possibilities for new meanings and knowledges to emerge.